Assessing Tasks: The Case of Interactional Difficulty. (18th July 2017) - Pallotti, Gabriele
Abstract: This article is a conceptual and methodological exploration of a new construct, task interactional difficulty, and of a possible approach to assessing task demands in general. After arguing for the use of 'task difficulty' instead of 'task complexity', the notion of task interactional difficulty is analyzed, first by reviewing previous SLA research, then by elaborating an explicit theoretical definition. An operationalization is suggested in terms of three dimensions: number of turn exchanges, number of initiating moves, and visual access among participants. The first two parameters can be measured on native speakers' task performance, while the third may be assessed with two categorical values. To demonstrate the feasibility of this approach, these measures are applied to a corpus of native speakers of Italian performing six different oral tasks, which are then ranked according to their interactional difficulty. Implications for SLA research and task-based language teaching and assessment are discussed, as well as possible ways of extending this procedure to other types of tasks and other facets of difficulty.